(untitled) (Journal of Partial Differential Equations, 2016)
" In this work an existence and uniqueness of solution of the non-local boundary value problemfor the loaded elliptic-hyperbolic type equation with integral-differential operations in double-connected domain have been investigated. The uniqueness of solution is proved by the method of integral energy using an extremum principle for the mixed type equations, and the existence is proved by the method of integral equations."